Tax Personal Data, Privacy and Access to Information contained in the Real State Registry: Proposing a Solution based on Taxpayers Rights: Propondo uma Solução Baseada nos Direitos dos Contribuintes - Navarro Schiappacasse, María Pilar; Magasich-Airola, Álvaro-Pablo (Revista Chilena de Derecho y Tecnología, 2023)
The Internal Revenue Service determines the Land Taxation and oversees its compliance. For so doing, it processes personal data of Real State landlords through collection and systematization to elaborate the Real State Registry. This work holds that the data contained in that registry is personal data. Thus, based on tax privacy and taxpayers´ right to have their personal data protected, legal consent should be needed to share their data with third parties. In addition, any technology resource used to update the Registry should not affect privacy due to its enshrinement in overseeing procedures.